Typification of the name Edraianthus siculus (Campanulaceae), endemic species from S-Italy - Di Pietro, Romeo; Fortini, Paola; Lakušić, Dimtar; Iamonico, Duilio (Phytotaxa, 2020)
Edraianthus (Candolle 1830: 130) Candolle (1839: 149) (Campanulaceae Juss.) is a genus of 10–14 species with a centre of distribution in the Balkans, while disjunctions occur in the central and southern Apennines (peninsular Italy), Sicily, and the southern Carpathians (Stefanović et al. 2008).